Clostridium perfringens type C causing necrotising enteritis. Issue 8 (August 1984) - Severin, W P; de la Fuente, A A; Stringer, M F
Abstract : A rapidly fatal case of enteritis necroticans in a 24 year old man with diabetes was caused by Clostridium perfringens type C. The role of beta toxin in the disease is discussed. This type has not been previously described as a causative agent in necrotising bowel disease of man outside endemic areas.